Evaluation Of Large-Scale Temperature Gradients To Support Assessment Of Convection And Cold-Trap Processes In Heated Drifts - R. W. Fedors; C. Manepally; L. B. Browning; G. R. Adams; S. T. Green (Society for Mining, Metallurgy & Exploration, 2004)
This paper provides estimates of large-scale temperature gradients that can be used to support modeling of natural convection and cold-trap processes in thermally perturbed drifts. Temperature influences estimates of the quantity and chemistry of water contacting engineered components (e.g., drip shields and waste packages) in a potential high-level waste repository at Yucca Mountain, Nevada. Temperature gradients drive natural convection and cold-trap processes, which could affect the distribution, quantity, and chemistry of liquid-phase water contacting drip shields (waste packages).The confluence of high temperatures, liquid-phase water, and high chloride may lead to corrosion of drip shields and waste packages. An overview of the evolution of environmental conditions in thermally perturbed drifts is presented to provide a context for the estimates of temperature gradients. A mountain-scale conduction-only model is used to estimate temperature gradients and temperature differences for a drift located at the center of a potential repository. Thermohydrologic models and heat transfer algorithms are used to evaluate the reasonableness of the conduction-only results. Estimates of temperature using an in-drift heat transfer algorithm account for the possibility of drift degradation and formation of a rubble pile on the drip shield. Temperature differences between the center and ends of the drift are estimated to rapidly increase to 80 °C soon after repository closure. That temperature difference decreases over time to 15 °C after 10,000 years. Local temperature gradients are generally estimated to be less than 0.2°C/m, though the gradients can be much larger near changes in lithology and near the end of the drift. The estimates of temperature gradients do not account for intermediate- and small-scale variations, such as those influenced by differences in heat loads between waste packages, intra-layer variations in thermal properties of the surrounding fractured rock, or localized drift degradation.